EFFECT OF OPPORTUNITY AND RATIONALIZATION ON FINANCIAL STATEMENT FRAUD IN DEPOSIT MONEY BANKS (DMBS) (Journal of Global Accounting, 2023)
This study examines the effect of opportunity and rationalization on the financial statement fraud pentagon of deposit money banks in Nigeria. The study adopts the ex post facto research design was used in the study. The population comprised thirteen (13) Deposit Money Banks listed on the Nigerian Exchange Group (NGX) as at end of 2021. To assure the homogeneity of the sample, the study uses the purposive sampling technique, which is predicated on the use of a comprehensive data set. The study made use of secondary source data. The sources were the audited yearly financial reports and account from 2012 to 2021. The Hausman test selected the random effects model over the fixed effects model. The results revealed that there is a significant (negative) relationship between opportunity and financial statement fraud in deposit money banks, rationalisation and financial statement fraud in deposit money banks. Based on this the study recommends that auditors review the availability of opportunities during the review of financial transactions. They should look for the tendency to rationalise that some employees have because it plays a role in the fraud. The results showed that the audit tasks of risk assessment, system audit, and financial report verification are very important when the psychological trait of rationalisation is well understood.
Keywords: Opportunity; Rationalisation; Financial Statement Fraud; Deposit Money Banks